The Influence of Product Experience on Customer Loyalty of Frozen Food Product - Utami, Made Fiona Dwi; Chaldun, Evy Rachmawati (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Indonesia’s frozen food industry is experiencing rapid development. Companies are targeting almost the same target market leads to tight competition. Therefore, many businesses concern about gaining customers while enhancing their customer loyalty. Dealing with a loyal customer is less costly and beneficial for any business. Product experience is one factor that could help to elicit a positive experience to enhance customer loyalty. This research limited to processed meat frozen food products such as sausage, chicken wings, nuggets, et cetera. It aims to get a better understanding of the product experience of a well-known brand, then investigate the influence of it on customer loyalty. Those understanding will be a helpful reference for a small and medium frozen food company with a similar product to design and manage their product experience to enhance their customer loyalty. The ultimate goal is to grow the business to the next level. The research used purposive sampling with 277 qualified quantitative data collected through an online questionnaire. The data were analyzed using multiple linear regression and shows that both hypotheses (aesthetic, meaning, and emotional experience is significant predictors of customer loyalty) are accepted. There is a significant influence of product experience (aesthetic experience, the experience of meaning, and emotional experience) on customer loyalty of frozen food products. The predictors able to explain 50.7% variations of customer loyalty, and experience of meaning became the highest predictors of the variation.Keywords: Customer loyalty, frozen food, small and medium enterprise, SMEs, product experience